2006
DOI: 10.1074/jbc.m513041200
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein A Directly Interacts with TLR4 and MD-2 and Regulates Inflammatory Cellular Response

Abstract: The purpose of the current study was to examine the binding of pulmonary surfactant protein A (SP-A) to TLR4 and MD-2, which are critical signaling receptors for lipopolysaccharides ( In innate immune systems, toll-like receptors (TLRs) 2 are implicated in recognition and signaling of pathogen-associated molecular patterns (1). Stimulation of different TLRs induces distinct patterns of gene expression, which leads to the activation of innate immunity and instructs the development of antigen-specific acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
1
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 55 publications
3
118
1
3
Order By: Relevance
“…SP-A binds to one or more receptors on macrophages (22) which triggers signaling events that alter the biology of these cells (28,46,47). Previous work from our laboratory has shown that SP-A increases MR expression on human MDMs, while another laboratory found that SP-A increases SR-A expression on rat macrophages (4, 5); both receptors are known PRRs.…”
Section: Sp-a Up-regulates Expression Of Tlr2 But Not Tlr4 On Humanmentioning
confidence: 97%
“…SP-A binds to one or more receptors on macrophages (22) which triggers signaling events that alter the biology of these cells (28,46,47). Previous work from our laboratory has shown that SP-A increases MR expression on human MDMs, while another laboratory found that SP-A increases SR-A expression on rat macrophages (4, 5); both receptors are known PRRs.…”
Section: Sp-a Up-regulates Expression Of Tlr2 But Not Tlr4 On Humanmentioning
confidence: 97%
“…In addition, SR-A is involved in combinatorial feedback inhibition of proinflammatory signaling mediated by Toll-like receptors (91). In this regard, anti-inflammatory activities of SP-A that were previously attributed to direct binding of SP-A to Toll-like receptors (92,93) may also involve indirect regulation of SR-A via SP-R210. It is noteworthy that TLR2 (Toll-like receptor 2) contributes to intracellular survival of S. aureus in macrophages (94).…”
Section: Cd11cmentioning
confidence: 99%
“…Collectins-The 1.13-kb cDNA for human SP-A1 and the 1.181-kb cDNA for human SP-D were inserted into pEE14 plasmid vectors, and recombinant human SP-A and SP-D were expressed in CHO-K1 cells using the glutamine synthetase gene amplification system (20), as described previously (10,21). CHO-K1 cells expressing SP-A and SP-D were grown in glutamate-free Glasgow minimum essential medium (Sigma) containing 10% dialyzed fetal calf serum and methionine sulfoximine (50 M for SP-A and 25 M for SP-D) for gene amplification.…”
Section: Methodsmentioning
confidence: 99%